Pengaruh Manajemen Kinerja Terhadap Produktivitas Kerja Pada Badan Amil Zakat Nasional Kota Serang - Zulina Ayunani, Faras; Latifah Jusdienar, Akka; Zahra Ulani, Siti (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Zakat, an obligation for eligible Muslims, serves as a wealth redistribution mechanism crucial for reducing economic disparities and aiding those in need. An effective, transparent zakat program can significantly boost Indonesia’s economic welfare. Amil Zakat not only collects and distributes funds but also supports and guides mustahik to enhance productivity and economic independence. To optimize productivity, it’s essential to improve administrative efficiency and Amil Zakat’s capacity to execute duties competitively and effectively. Training and capacity development for Serang City Zakat Amil are also vital for professional performance. Challenges to Amil Zakat’s productivity include managerial skill deficits, insufficient resources, and an inefficient support system, compounded by unstable economic conditions or low education levels. Effective performance management, incorporating performance measurement, impact analysis, and stakeholder feedback, is crucial for ensuring the zakat program meets its goals and achieves the desired impact. This quantitative research, employing surveys, questionnaires, and observation, utilized SPSS version 29 for statistical analysis. Results showed that a unit increase in performance management leads to a 0.687 increase in work productivity, with a significant positive relationship between the two variables. Hypothesis testing indicated that performance management significantly affects productivity, with a calculated T value of 8.431 and a significance level of 0.001, confirming the impact of performance management on employee productivity